ANALISIS PERBEDAAN KEBUTUHAN BERPRESTASI DOSEN AKUNTANSI UPN “VETERAN” JAWA TIMUR - Mustika, Rina (Journal of Accounting and Strategic Finance, 2009)
One of the objectives of graduate  accounting educatin is to create educated employees and professionalism on their fields. Since the part of creating professionalism process can be achieved through education, graduate education must accommodate for this purpose. Professionalism is an attitude or a spirit to maintain professional status and public appearance upon themselves, and persistently studying the knowledge and the substance of the work they possessed. The role of graduate education is to transform academic or non-academic staff structurally and systematically. Professionalism illuminates accountant as a lecturer that they must have mastered and implemented knowledge, skill, and character. According to work orientation need theory, individual seldom be influenced by needs like need for achievement, need for power, and need for affiliation. The lecturer’s needs may also be influenced by work domain, which is the hierarchy and also gender. This study used independent t-test to know the difference of the need of achievement for 35 lectures of accounting program UPN “Veteran” East Java on the point of view of lecturer’s type, hierarchy, gender, and personal biographies characteristic. The result indicated that there was no difference of the need of archievement among accounting program lecturers.   Keywords: Lecturer’s type, hierarchy, personal biographies characteristic, need of achievement.